PERLINDUNGAN SATWA APPENDIX DAN LINGKUNGAN OLEH PEMERINTAH DAERAH TANJUNG RIAU, BATAM: Protection of Appendix Species and the Environment by the Local Government of Tanjung Riau, Batam - Reggy Fazrin Febrian; Ninuk Wijiningsih (Faculty of Law, Trisakti University, 2025)
Indonesia has both constitutional and international responsibilities to conserve the environment and wildlife, including species listed in the CITES Appendix. Batam City, especially the Tanjung Riau industrial area, is particularly vulnerable to illegal wildlife trade due to its strategic location along cross-border routes. This study aims to examine the legal obligations and the implementation of policies by the Batam City Government in protecting Appendix species and the environment, as regulated under Regional Regulation No. 8 of 2014 and other relevant laws. The research applies a normative juridical method with a descriptive approach, using secondary data analyzed qualitatively and concluded deductively. The findings indicate that protection efforts by local authorities, including BBKSDA and related agencies, remain sectoral and fragmented, lacking adequate human resources and infrastructure support. Institutional coordination, public participation, and monitoring systems in industrial zones are still considered ineffective. The study concludes that current protection measures for Appendix species in Batam are not yet optimal. Therefore, there is a need for strengthened local regulations, adoption of modern surveillance technologies, institutional capacity-building, and increased public engagement to ensure long-term and effective conservation of protected species.